2012
DOI: 10.1007/s11284-012-0927-7
|View full text |Cite
|
Sign up to set email alerts
|

Post‐dispersal seed removal in four Mediterranean oaks: species and microhabitat selection differ depending on large herbivore activity

Abstract: Quercus forest regeneration is limited by different factors, post‐dispersal predation being one of the most critical stages. We analysed seed removal of four coexisting Quercus species (Q. ilex, Q. suber, Q. faginea and Q. pyrenaica) in a Mediterranean forest located in Southern Spain. Marked and weighed acorns from each of the species were placed in experimental units with or without exclusion of large herbivores and in two microhabitat types (Q. ilex shade or open). Acorn removal was monitored for 120 days i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In addition, it has been reported that differences among seeds caused by seed nutrient content, physical and chemical defense mechanisms (e.g., shell hardness, presence of secondary metabolites, etc.) affect the preference of seed feeders [30]. However, our initial hypothesis that germinated seeds would be less favorable for seed consumers was rejected, as no significant differences on seed predation rates between fresh and germinated seeds were detected in the long term (more than two months after direct sowing).…”
Section: Seed Predation As the Main Cause Of Establishment Failurementioning
confidence: 98%
“…In addition, it has been reported that differences among seeds caused by seed nutrient content, physical and chemical defense mechanisms (e.g., shell hardness, presence of secondary metabolites, etc.) affect the preference of seed feeders [30]. However, our initial hypothesis that germinated seeds would be less favorable for seed consumers was rejected, as no significant differences on seed predation rates between fresh and germinated seeds were detected in the long term (more than two months after direct sowing).…”
Section: Seed Predation As the Main Cause Of Establishment Failurementioning
confidence: 98%
“…Gómez et al 2003;González-Rodríguez and Villar 2012). These traits are often associated with animal activity, either seed predation or dispersal (Sork 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, sympatric seeds may differ notably in palatability and nutrition value (Vander Wall 1990). To survive and reproduce, seed-eating animals had developed numerous adaptations in treating and consuming various sympatric seeds , González-Rodríguez & Villar 2012, Yang et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out so far on seed selection and dispersal of sympatric seeds by rodents are limited , González-Rodríguez & Villar 2012, Yang et al 2012, Rusch et al 2013) and far from fully depicting the wide variation in the hoarding behavior of rodents in different geographical areas. Hull thickness has been reported to significantly affect seed dispersal , while other investigations have obtained conflicting result (Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation